Clinical profile and treatment outcome of acute intussusception among children in eastern Ethiopia: A seven years retrospective study - Tesfaye, Dawit Desta; Adem, Burka Mohammed; Ketema, Indeshaw; Mehadi, Ame; Eshetu, Bajrond; Teshager, Tilahun; Asfaw, Henock; Desalew, Assefa (Frontiers in Pediatrics, 2022)
Background Acute intussusception is the main cause of abdominal surgical emergencies worldwide in young children, with an incidence of approximately 1 to 4 per 2,000 children. An accurate estimate of the treatment outcomes of acute intussusception in children is unknown in low-and middle-income countries like Ethiopia. Hence, this study aimed to determine the clinical profile, treatment outcomes of acute intussusception and its associated factors among children admitted to Hiwot Fana Specialized University Hospital in eastern Ethiopia. Methods An institutional-based retrospective cross-sectional study was conducted from November 01 to 30, 2021, among children admitted and managed for acute intussusception. All medical records of children admitted and managed for acute intussusception at Hiwot Fana Specialized University hospital between January 2014 and December 2020 were included. Data were collected using pretested structured checklists through a review of medical records, entered and analyzed using Statistical Package for Social Sciences version 25.0. Chi-square (χ2) tests were applied to determine the associated factors with treatment outcome. The statistical significance was considered at a p-value < 0.05. Results In this chart review of children, 13.3% (95% CL: 11.8–14.8) died. The median age of the study participant was 13 months. The majority, 72% were male and 76% were less than 24 months old. Regarding the clinical profile; abdominal pain (94.7%), vomiting (93.3%), bloody diarrhea (70.7%), and abdominal distention (76.0%) were the most common clinical presentations. Age less than 24 months [X2 = 8.13 (df = 1); p = 0.004], preoperative vital signs [X2 = 19.21 (df = 2); p = 0.000], intraoperative findings [X2 = 18.89 (df = 1); p = 0.000], and postoperative complications [X2 = 14.60 (df = 1); p = 0.000] were significantly associated with treatment outcome of acute intussusception. Conclusion In this chart review, the overall mortality rate in children was relatively high. One in seven children died from acute intussusception. Age less than 24 months, preoperative vital signs, intraoperative findings, and postoperative complications were significantly associated with acute intussusception treatment outcomes. Surgical management was the only treatment performed in all cases. Delayed presentation of patients and lack of other treatment modalities such as non-surgical interventions are serious concerns in this facility. The initiation of non-surgical reduction may reduce the need for surgical intervention-related complications, and child mortality.